Cara Mengatasi Masalah Pada Siswa SMP Yang Terindikasi Conduct Problem - Novita Luthfiana, Dhini; , Usmi Karyani S.Psi, M.Si., Psi (2017)
Abstract Adolescence is a development phase is very important, starting with the physical to emotional maturity. Emotional maturity affected by mental health. Various research about mental health showed too much adolescents who experience emotional distress to the conduct problem. Based on the first results of Junior High School A from 227 students, 40 students indicated conduct problems. Someone who indicated conduct problem have coping skills that dissatisfactory development because they have difficulty in cognitive development. This study aims to determine the dynamics of stress coping used of Junior High School students who indicated conduct problems. This research use purposive sampling with the characteristics of Junior High School students who indicated conduct problems high level, sample of this research are six students. Data collection tool in this research is a semi-structured interview. The results showed that the source of the problems often experienced by junior high school students is friendship, academic and family. When they have a problem, the participants cause the problem is friend, brother and themselves. Participants who solved the problem are friends, parents, siblings and online media. Then, stress coping used of students who indicated conduct problems is adaptive by seeking social support for instrumental and active behavior, than maladaptive by confrontive, acceptance, mental disengagement and minimization. Suggestion for the school is to create policies that govern peer counseling and advice for parents to be close to the child. Keyword: Coping, Conduct Problem, Adolescence